Social Workers and Resilience Revisited. Issue 2 (15th March 2017) - Collins, Stewart
Abstract : The topic of social workers and resilience has received a considerable amount of attention in social work research and literature in recent years. Resilience has also been incorporated into the 'official discourse' of social work education and practice. However, many definitions of the concept have been offered. It has been also subject to some criticism, primarily because of the alleged focus on the individual worker at the expense of the structural, political, policy and organisational context. This paper critically reviews research focused on resilience, social work students and social workers. Implications for social work education, social work organisations and social work practice are explored. Consideration is given to developing social work students, social workers and social work managers' knowledge and understanding of resilience and the means to maintain and develop resilience, based on wide ranging ecologically based approaches and by locating the topic within a broader theoretical context.